Metode-Metode Pembelajaran Rasullullah SAW Dalam Kitab Hadis Tarbawi - Huljannah, Mifta; Kanus, Oktari (An-Nuha, 2023)
Islam pays a significant portion of attention to education in every phase of a child's life development. Starting from the period of formation of the fetus in the womb, breastfeeding, childhood, adolescence to adulthood. To make it all happen, every child needs someone who helps his development and fulfills all his needs well. Besides that, the environmental conditions are right and appropriate for his association and psychological development as well as self-development with a good education. So parents, educators/teachers, and the environment have a very big role in this. Educational materials and methods are in accordance with Islamic concepts, especially the concept of hadith, which is a necessity to be applied in educating children to support the successful achievement of educational goals, namely to form children with noble personalities.